“The Gifts and the Calling of God are Irrevocable” (Romans 11:29): If So, How Can Paul Declare that “Not All Israelites Truly Belong to Israel” (9:6)? - Nanos, Mark D. (Studies in Christian-Jewish Relations, 2016)
The translation(s) of Romans 9:6 have undermined the premise in verses 1-5 and in chapter 11 of an irrevocable covenant with Israelites regardless of whether they agree with Paul about Jesus (at the time that he was writing his argument in Romans). The traditional interpretive results challenge not only Paul's arguments but also a central feature of post Nostra Aetate 4 developments in Christian discourses about Jews. The context of Paul's arguments in chapters 9-11 are discussed for determining the most likely translation choices in the context of 9:6 and then for the verse itself. Two probable alternatives are offered, both of which offer a way to read this text to corroborate that Paul upheld the continued validity of Israelite identity for his peers, and to undermine the traditional role of this text in the replacement theological arsenal.